Nano-bioceramics : process routes and characterization - Xu, Jinling (2008)
((This thesis is divided into 2 portions. Part 1: Chapter 1-6). The present research was carried out to explore modified bioceramic materials with suitable bioactive properties for tissue bonding. The focus concerned improving bio-mechanical performance of the synthetic calcium phosphates especially hydroxyapatite (HA, Ca10(PO4)(OH)2). To attain this purpose, suitable processing techniques were pre-requisite.